The Role of Urban Community Leaders in Local Product Development Using Intellectual Capital: A Case Study of Bangkok, Thailand - Phukamchanoad, Phusit; Palapin, Pennapa; Supromin, Chaimongkhon (Journal of Ecohumanism, 2024)
This research investigates the role of urban community leaders in leveraging local intellectual capital for the design and development of community products. It examines how these leaders contributed to creating products that fostered self-sufficiency within their communities. Data were collected from 43 communities across 5 sub-districts in Dusit District, Bangkok, involving a total of 453 participants. The study employed a combination of explanatory and interdisciplinary research methods. The findings revealed that community leaders significantly contributed to accumulating intellectual capital for product development. Especially, the highest engagement observed in collective brainstorming sessions. The most actively engaged leaders were female, aged 40 years. In contrast, self-reliant leaders, who typically held bachelor’s degrees, exhibited cautious spending habits and a commitment to community rules and self-reliance without government support. Community leaders collaboratively designed the Dusit Brand logo and proposed a seven-stage process for urban community product development. This process includes incorporating local wisdom, reflecting community identity, fostering public participation, developing local knowledge, exhibiting products, building community reputation and recognition, and achieving community standards. The research highlights that sustainable community products are created through a process of understanding, accessing, and developing the local economy and society, with a focus on enhancing social quality for sustainability.